2016
DOI: 10.1007/s00421-016-3391-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise effects on aortic wave reflection derived from wave separation analysis in young- to middle-aged pre-hypertensives and hypertensives

Abstract: In young-to-middle-aged pre-hypertensive and hypertensive individuals, aortic backward waves decrease post-exercise; this change is not reflected in brachial BP measurements and is poorly indexed by measures of pressure augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 46 publications
5
17
1
1
Order By: Relevance
“…This result seems unrelated to post-exercise BP changes, as no significant and sustained increases in aortic or brachial BP were evident (Table 2 ). Differences in exercise modes and intensities, populations and timing of assessment make comparisons between the present and prior studies difficult, but the current results indicated that RES altered the magnitude of wave reflection, and that these were not associated with changes in central and peripheral BP, as suggested previously (Millen et al, 2016 ).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This result seems unrelated to post-exercise BP changes, as no significant and sustained increases in aortic or brachial BP were evident (Table 2 ). Differences in exercise modes and intensities, populations and timing of assessment make comparisons between the present and prior studies difficult, but the current results indicated that RES altered the magnitude of wave reflection, and that these were not associated with changes in central and peripheral BP, as suggested previously (Millen et al, 2016 ).…”
Section: Discussionsupporting
confidence: 61%
“…Although stimulation of the sympathetic nervous system presumably also occurred during AER, the vasoconstrictive effect may have been markedly reduced (Heffernan et al, 2007a ) as distinct and exercise-mode dependent, shear stress patterns have been reported to affect vasoconstriction (Thijssen et al, 2017 ). Most studies to date, including the current study, have reported a reduction in AIx following AER (Kingwell et al, 1997 ; Heffernan et al, 2007a ; Munir et al, 2008 ; Millen et al, 2016 ) with this result potentially linked to increased peripheral vasodilation rather than sympathetic nervous system-induced vasoconstriction. Vasodilation has been shown to occur in the presence of sympathetic activation with the endothelium-mediated vasodilator effect overriding the neural vasoconstrictor effect during AER (Piepoli et al, 1993 ).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These observations are the first in older individuals and are similar to the responses recently reviewed in healthy younger adults (Mutter et al, 2017). While resting measures of arterial stiffness reflect structural and functional mechanisms, beneficial reductions in arterial stiffness during recovery following acute exercise in healthy adults are suggested to be functional and are likely mediated by reductions in central blood pressure (Millen et al, 2016), vasoconstrictors (endothelin-1) (Schreuder et al, 2014) and sympathetic nerve activity (Heffernan et al, 2007), alongside increases in nitric oxide bioavailability and endothelial function (Campbell et al, 2011). Elevations in arterial stiffness following exercise in obese and hypertensive adults (Shim et al, 2011;Gkaliagkousi et al, 2014;Moon et al, 2015;Bunsawat et al, 2017) are potentially detrimental and may be due to underlying dysfunction of these mechanisms.…”
Section: Variablesupporting
confidence: 78%